Seed and seedling surface-sterilization for in vitro culture of tillandsia gardneri (Bromeliaceae) - Pinto, A. C R; Demattě, M. E S P [UNESP]; Creste, S.; Barbosa, J. C. [UNESP] (My University, 2012)
Tillandsia gardneri is a bromeliad with ornamental value and a wide geographical distribution over Brazil. However, due to habitat loss and illegal overcollection in the wild it is included as a vulnerable species in the official list of endangered plants of the State of Rio Grande do Sul, Brazil. The development of a protocol for T. gardneri seed propagation in vitro may be useful for reintroducing plants in their natural habitats, and for germplasm conservation. A difficult problem encountered during the establishment of an in vitro culture is explants disinfection, especially when working with endangered species, from which explant availability is restricted. Thus, the establishment of a sterilization protocol is crucial for the initiation and success of a micropropagation system for T. gardneri. The objective of this study was to evaluate the effect of sodium hypochlorite concentration and exposure time in seed and seedling surface disinfection, tissue sensitivity and development. Sodium hypochlorite solutions (10 or 20%/5, 10 or 15 min; 25%/5 or 10 min; and 50%/5 min) were effective in eliminating seed superficial contaminants. There was no significant difference among the effective sterilization treatments in relation to seed germination (%), and seedling length and number of leaves, after 120 days in vitro. Also, no damage to seed and seedling tissues were observed. Surface sterilization of seedlings, for initiation of an in vitro culture, required higher concentrations of sodium hypochlorite (25%/15 min; 20 or 50%/5, 10 or 15 min; and 40%/5 and 10 min) for controlling fungal and yeast contamination, compared to seed sterilization. No significant differences among these treatments were found in relation to seedling length and number of leaves, after 60 days in vitro.
Keywords: Conservation; Disinfection; Micropropagation; NaOCl; Sodium hypochlorite; Bromeliaceae; Tillandsia; Tillandsia gardneri